UPAYA DAKWAH JAM’IYYAH RUQYAH ASWAJA DI KECAMATAN BANGUNREJO TAHUN 2019-2020 - Khotimah, Amiyati Khusnul; Sabdo, Sabdo; Rohman, Fathur (Universitas Muhammadiyah Metro, 2020)
Ruqyah is one of the treatment oldest methods on earth before medical development. At first, ruqyah is forbidden because it contains elements of shirk.However, after the arrival of Islam and the revelation of the Qur'an, the ruqyah treatmentmethod was adjusted to the Islamic Shari'a which was certainly far from the element ofshirk. So, ruqyah is allowed even recommended as in Surah Al-Isro 'verse 82. This undergraduate thesis is titled